انسان کی تخلیق اورآغاز و ارتقا: سائنسی نظریات اور اسلامی تعلیمات کے تناظر میں ایک مطالعہ: Creation, Origin and Evolution of Man: A Study in the Context of Scientific Theories and Islamic Teachings (Al-Qamar, 2022)
In the past, when the sciences were in the early stages of conjecture, the search for authenticity was the only source of truth for those who were religious and inferior. Religions in the past, in turn, provide answers to real and potential questions. Therefore, all religions are considered to be the creators and protectors of the universe in their time as well as the destroyers, and such an idea is in fact the basis of the theory of creation. With the advancement of science, there have been real changes in the tendency of human thought. In modern times, religions have not been able to achieve that ancient demand and prestige. Enlightened people have gradually broken away from religion and made science the focus of their attention. According to the theory of scientists, in the past only matter was matter and it also spread. Without oxygen (O2), life on Earth would not be possible without it, nor would the name of hydrogen, nor any form of plants, nor any map of animals be just elementary particles of matter. Which were scattered throughout the universe. These particles cause the earth to shake, as if the earth were shaken by an earthquake. The movement was so strong that it shook every single particle of it in the same way that a wind blows dust and sand particles from one place to another, and this is the condition that arose in the early days. He threw all these particles away and mixed them together in such a way that everything in the universe came into being and became water in this movement which is an essential part of life. Hydrogen and oxygen were also produced.
Keywords: Evolution of Man; Scientific Theories; Origin; Islamic Teachings